High SARS-CoV-2 seroincidence but low excess COVID mortality in Sierra Leone in 2020-2022. - Ahmed Osman; Ashley Aimone; Rashid Ansumana; Isaac Bogoch; Hellen Gelband; Karen Colwill; Anne-Claude Gingras; Marc-André Langlois; Ronald Carshon-Marsh; Ibrahim Bob Swaray; Amara Jambai; Mohamed Vandi; et al. (PLOS Global Public Health)
While SARS-CoV-2 infection appears to have spread widely throughout Africa, documentation of associated mortality is limited. We implemented a representative serosurvey in one city of Sierra Leone in Western Africa, paired with nationally representative mortality and selected death registration data. Cumulative seroincidence using high quality SARS-CoV-2 serological assays was 69% by July 2021, rising to 84% by April 2022, mostly preceding SARS-CoV-2 vaccination. About half of infections showed evidence of neutralizing antibodies. However, excess death rates were low, and were concentrated at older ages. During the peak weeks of viral activity, excess mortality rates were 22% for individuals aged 30-69 years and 70% for those over 70. Based on electronic verbal autopsy with dual independent physician assignment of causes, excess deaths during viral peaks from respiratory infections were notable. Excess deaths differed little across specific causes that, a priori, are associated with COVID, and the pattern was consistent among adults with or without chronic disease risk factors. The overall 6% excess of deaths at ages ≥30 from 2020-2022 in Sierra Leone is markedly lower than reported from South Africa, India, and Latin America. Thus, while SARS-CoV-2 infection was widespread, our study highlights as yet unidentified mechanisms of heterogeneity in susceptibility to severe disease in parts of Africa.